Nesting of periodical groups into simple periodica groups - Olshansky , A. Yu.; Ольшанский , А. Ю. (Institute of Mathematics, NAS of Ukraine, 1992)
It is proved that each periodic group is isomorphic to a subgroup of some simple periodic group.